Overvaluation of Weight or Shape and Loss-of-Control Eating Following Bariatric Surgery - Ivezaj, Valentina (Obesity (Silver Spring), 2019)
OBJECTIVE: Little is known regarding overvaluation of weight/shape, a key cognitive feature of eating disorders, among individuals with disordered eating following bariatric surgery. This study examined the significance of overvaluation of weight/shape among post-bariatric surgery patients with loss-of-control (LOC) eating. METHODS: Participants were 145 individuals who underwent sleeve gastrectomy within the previous six months and reported regular LOC eating. Overvaluation of weight/shape, LOC eating, and eating-disorder psychopathology were assessed using the Eating Disorder Examination (EDE)-Bariatric-Surgery-Version interview; depressive symptoms and disability were assessed by the Beck Depression Inventory (BDI-II) and Sheehan Disability Scale (SDS), respectively. RESULTS: Overvaluation of weight/shape, examined continuously, was correlated significantly with higher levels of eating-disorder psychopathology (EDE), depression (BDI-II) and disability (SDS). Categorically, using established clinical cut-points, relative to the Subclinical Overvaluation group (n=70, 48.3%), the Clinical Overvaluation group (n=75, 51.7%) reported significantly greater frequency of LOC eating episodes and higher EDE, BDI-II, and SDS scores. The two groups did not differ significantly in current BMI or percent weight-loss following surgery. CONCLUSION: Our findings, which highlight the clinical significance of overvaluation of weight/shape among patients with LOC eating following bariatric surgery, are similar to those previously reported for binge-eating disorder. Post-operatively, overvaluation of weight/shape was associated with greater eating-disorder psychopathology, depression, and disability.